Theoretical analysis and optimal design of permanent magnet assisted magnetic gears - SHANGGUAN Xuanfeng; LI Shihao; ZHANG Longqi; ZHAO Lei (Jixie chuandong)
ObjectiveAiming at the problems of low structural strength of surface-mounted magnetic gears and large torque pulsation of convex pole magnetic gears, a permanent magnet assisted magnetic gear was proposed.MethodsFirstly, the basic structure and working principle of the magnetic gear were introduced. The inner rotor adopted a rotor structure similar to that of a permanent magnet assisted reluctance motor. Secondly, an analytical formula for calculating the magnetic flux density distribution of the internal and external air gaps of magnetic gears was derived and obtained, and the characteristics of magnetic gears were analyzed. Finally, multi-objective optimization design was carried out with the goal of increasing the electromagnetic torque and reducing the torque ripple.ResultsIt provide a reference for the design of magnetic gears assisted by permanent magnets.